Methodius von Olympus: De lepra Edition des griechischen und des slavischen Textes mit einer Einleitung und einer deutschen Übersetzung - Methodius Olympius 230-311; Jouravel, Anna 1982-; Sieber, Janina 1988-; Bracht, Katharina 1967- (Berlin Boston De Gruyter, 2024)
"This volume is the first to make the full text of De lepra by church father Methodius of Olympus (d. 311 CE) available in a critical edition, both in its original language, Greek, and in the much more extensive Old Slavic translation from the tenth century CE. Both text critical editions are supplemented with a German translation and an introduction."--
Literaturverzeichnis: Seite 67-73
Textbeispiele in altslavisch
Keywords: Methodius -- of Olympus, Saint -- -311; LEPROSY in the Bible -- Early works to 1800; Theology -- Early works to 1800; Lèpre dans la Bible - Ouvrages avant 1800; Théologie - Ouvrages avant 1800; Quelle